1997
DOI: 10.1111/j.1348-0421.1997.tb01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Vibrio cholerae O1 Isolated from Sporadic Cholera Cases in Okinawa, Japan

Abstract: In July 1994, 6 cholera cases due to Vibrio cholerae O1 El Tor Ogawa sporadically appeared in Okinawa. All 6 patients had no history of traveling abroad. In the period of this cholera outbreak, a strain of V cholerae O1 El Tor Ogawa was detected from an imported fish at the Naha port quarantine station. The isolates were characterized to clarify whether or not, they belonged to a common clone. Phenotypes were identical except that one strain revealed cured Celebes and the others were original Celebes in kappa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This sequence was used for constructing new primers (inv 1 and inv2) applied in inverse PCR (13), using as template self-ligated DNA fragments. Further sequencing was extended by PCR walking (42) using random primer AP 40 (16), and by LA PCR Cloning Kit (TaKaRa Biomedical, Ohtsu, Japan). All primers used in this study are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence was used for constructing new primers (inv 1 and inv2) applied in inverse PCR (13), using as template self-ligated DNA fragments. Further sequencing was extended by PCR walking (42) using random primer AP 40 (16), and by LA PCR Cloning Kit (TaKaRa Biomedical, Ohtsu, Japan). All primers used in this study are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Two possible starting methionine codons were present at nucleotide position 1 and 10. Therefore, this ORF was composed of 486 bp or 477 bp that encode a polypeptide of 162 aa or 159 aa with a calculated Mr of 16,535 Da or 16,192 Da, which was smaller than the Mr calculated by SDS-PAGE for the purified pilin (20 kDa) (Fig. 2).…”
Section: Dna Sequencing and Analysismentioning
confidence: 99%